2001
DOI: 10.1074/jbc.m009664200
|View full text |Cite
|
Sign up to set email alerts
|

The Bloom's Syndrome Protein (BLM) Interacts with MLH1 but Is Not Required for DNA Mismatch Repair

Abstract: Bloom's syndrome (BS) is a rare autosomal recessive disorder characterized by pre-and postnatal growth deficiency, immunodeficiency, and a tremendous predisposition to a wide variety of cancers. Cells from BS individuals are characterized by a high incidence of chromosomal gaps and breaks, elevated sister chromatid exchange, quadriradial formations, and locus-specific mutations. BS is the consequence of mutations that lead to loss of function of BLM, a gene encoding a helicase with homology to the RecQ helicas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
88
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(93 citation statements)
references
References 29 publications
4
88
1
Order By: Relevance
“…The human Bloom syndrome helicase (BLM), a component of BASC, was shown to directly interact with MLH1 [71]. It has been hypothesized that MSH4-MSH5 and MLH1-MLH3 complexes promote the formation and stabilization of Holliday junctions and their preferential resolution into cross-overs rather than non cross-overs [72].…”
Section: Discussionmentioning
confidence: 99%
“…The human Bloom syndrome helicase (BLM), a component of BASC, was shown to directly interact with MLH1 [71]. It has been hypothesized that MSH4-MSH5 and MLH1-MLH3 complexes promote the formation and stabilization of Holliday junctions and their preferential resolution into cross-overs rather than non cross-overs [72].…”
Section: Discussionmentioning
confidence: 99%
“…In mammalian cells, about half of all DNA DSB are repaired by mechanisms involving HRR (Liang et al, 1998). As cell extracts lacking functional BLM helicase activity are competent for DNA MMR (Langland et al, 2001), the interaction of BLM with mismatch proteins may be significant for specific DNA events, for example, HRR, independent of the repair of single DNA mismatches. Studies using a yeast model system suggest that MSH2 and the SGS1 helicase play a significant role in HRR (Marsischky et al, 1999;Evans et al, 2000;Frei and Gasser, 2000;Myung et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…BLM associates with other proteins involved in DNA repair such as BRCA1, ATM, hMLH1, hMSH2, hMSH6, and replication factor C to form a complex called BASC that was isolated from p53-deficient HeLa cells (Wang et al, 2000). BLM binds directly to hMLH1, but is not required for DNA MMR (Langland et al, 2001;Pedrazzi et al, 2001). The Saccharomyces cerevisiae homolog of BLM, SGS1, suppresses genomic instability and homologous recombination (Myung et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Since BS cells are not deficient in MMR, it has been proposed that the hMLH1 interaction with BLM may play a role in HR (Langland et al, 2001;Pedrazzi et al, 2001). In this study, we set out to test whether BLM interacts also with other components of the MMR system.…”
mentioning
confidence: 99%
“…We and others have recently demonstrated that BLM interacts directly with the MMR protein hMLH1 (Langland et al, 2001;Pedrazzi et al, 2001). Since BS cells are not deficient in MMR, it has been proposed that the hMLH1 interaction with BLM may play a role in HR (Langland et al, 2001;Pedrazzi et al, 2001).…”
mentioning
confidence: 99%